Dielectric Behavior Of Binary Solutions Of Thermacol In Organic Solvents (Journal of Bangladesh Academy of Sciences, 2012)
The static dielectric constant and dielectric loss for the binary solutions of thermacol in various organic solvents have been measured varying the concentration of solute. The dielectric constant varied linearly with the concentration of solute, whereas the dielectric loss showed excess peak at a certain concentration of the solute for binary solutions. The authors also performed the first-principles calculations to study the equilibrium configurations of ethyl acetate and n-butyl acetate and estimated dipole moments. The experimental values of dipole moment for ethyl acetate and n-butyl acetate agreed fairly well with those calculated from first-principles. Key words: Dielectric constant; Dielectric loss; Binary solution; Dipole moment DOI: http://dx.doi.org/10.3329/jbas.v35i2.9427 JBAS 2011; 35(2): 211-220